Lazy lion - Mwenye Hadithi; Kennaway, Adrienne, 1945- (Glenview, Ill. : ScottForesman, 1993)
A lazy and demanding lion orders the animals of his kingdom to build him a house before the Big Rain comes.
"Celebrate reading! Scott Foresman 1D"--Cover.
First published: Great Britain : Hodder & Stoughton Children's Books, 1990.
K-3.
Keywords: Animals -- Habitations -- Fiction; Laziness -- Fiction; Lions -- Fiction; Animals -- Fiction; Laziness -- Fiction; Lions -- Fiction; Africa -- Fiction; Africa -- Fiction